2021
DOI: 10.1111/hepr.13600
|View full text |Cite
|
Sign up to set email alerts
|

Impact of antiviral therapy on risk prediction model for hepatocellular carcinoma development in patients with chronic hepatitis B

Abstract: Aim Risk prediction models for hepatocellular carcinoma (HCC) development are available. However, the influence of antiviral therapy (AVT) on these models in patients with chronic hepatitis B is unknown. Methods The dynamic changes in risk prediction models during AVT and the association between risk prediction model and the risk of chronic hepatitis B‐related HCC development were investigated. Between 2005 and 2017, 4917 patients with chronic hepatitis B (3361 noncirrhotic, 1556 cirrhotic) were recruited. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Multiple risk prediction models have been developed for the study of HCC prevalence in HBV patients[ 96 ]. Some of these models include individual prediction model, Chinese University-HCC, Guide with Age, Gender, HBV DNA, Core Promoter Mutation and Cirrhosis-HCC, Risk Estimation for Hepatocellular Carcinoma in Chronic HBV and Nomogram-HCC[ 97 ]. Arends et al [ 98 ] noted that HCC incidence is lower in patients who have received antiviral therapy, even though it did not eliminate the risk: The reported 5-year cumulative incidence rate of NCHCC was 2.1%.…”
Section: Treatmentmentioning
confidence: 99%
“…Multiple risk prediction models have been developed for the study of HCC prevalence in HBV patients[ 96 ]. Some of these models include individual prediction model, Chinese University-HCC, Guide with Age, Gender, HBV DNA, Core Promoter Mutation and Cirrhosis-HCC, Risk Estimation for Hepatocellular Carcinoma in Chronic HBV and Nomogram-HCC[ 97 ]. Arends et al [ 98 ] noted that HCC incidence is lower in patients who have received antiviral therapy, even though it did not eliminate the risk: The reported 5-year cumulative incidence rate of NCHCC was 2.1%.…”
Section: Treatmentmentioning
confidence: 99%
“…Nevertheless, high-risk patients still have a higher risk of HCC development despite a significant reduction in the risk score than low-risk patients who experience no changes in the risk score. 43 There are some limitations to our study. First, this was a single-center retrospective study.…”
Section: Discussionmentioning
confidence: 94%
“…We read with great interest the study by Chon et al 1 The authors demonstrated a hepatocellular carcinoma (HCC) prediction model of Chinese University-HCC (CU-HCC) score decreased significantly at 1 year after nucleoside/nucleotide analog (NA) therapy, but CU-HCC score at 1 year after NA therapy was an independent predictor of HCC development.…”
Section: Diagnostic Accuracy Of Hepatocellular Carcinoma Risk Prediction Models During Antiviral Therapy In Chronic Hepatitis B Patientsmentioning
confidence: 99%
“…The other authors have no conflicts of interest to declare. Nobuharu Tamaki 1,2 Masayuki Kurosaki 1 Sakura Kirino 1 Namiki Izumi 1 1…”
Section: Conflicts Of Interestmentioning
confidence: 99%